Mechanical structure design and analysis of the outside needle pipe climbing robot. (January 2022) - Gao, Guohua; Du, Xinyue; Feng, Yongbing; Wang, Shuangyou; Wang, Fuli; Zhang, Zihua
This study designed a crawling mechanism that can solve the measurement problems of slender and needle pipes by detecting the heating vertical needle pipe, which is greatly applied in the petrochemical and refinery industry. The robot's walking system uses a single driven wheel to stick on the way, with a scissor-hand structure to adapt to changes in diameter between 50 and 90 mm. This study lists the dynamic analysis equation of the robot, thereby obtaining the optimum range of Angle α between the horizontal line and the center line of the main driving wheel and the main clamping wheel. Moreover, the study uses multi-body dynamics simulation software for dynamics simulation analysis. Results indicate that the crawling system has the advantages of anti-deviation, can adapt to different pipe diameters and has a simple structure.